A How To Guide For Medical Students - Gillis, Andrea; Aarons, Cary B.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2024)
This book will provide a guide for medical students to self-reflect, build a portfolio, and select a career path equipped with the knowledge to make an informed decision that is the best for them. The editors comprise a diverse spectrum from background, stage of training, type of practice, to career path. This is a timely update taking into account new situations such as the virtual environment for residency applications, the spotlight on residency wellness, and incorporating diversity, equity, and inclusion in our personal and institutional missions.
Part I: Exploring Surgical Specialties and Practice Settings -- Assessing Your Interests, Skills, and Values -- Choosing a Surgery Training Environment: Military Programs -- Independent Programs -- Choosing a Surgical Training Environment: Rural Surgery Programs -- Choosing a Training Program: University-Based Programs -- Overview of the Surgical Subspecialties: Plastic & Reconstructive Surgery -- Overview of the Surgical Subspecialties: Vascular Surgery -- So you want to be a Cardiothoracic Surgeon? -- Maximizing the Clinical Years in Medical School A Fourth Year Student's Perspective Preparing for Surgical Training -- Part II: Navigating the Residency Application Process -- Developing a Competitive Residency Application -- Navigating the Residency Application Process: Understanding the Updates to the Recruitment Process -- Navigating the Residency Application Process: Preparing for both Virtual and In-Person Residency Interviews -- Navigating the Residency Application Process: A Recent Applicant's Perspective on Choosing a Residency Program -- Part III: Excelling in Surgical Training -- Developing Clinical and Technical Skills -- Utilizing Technology and Simulation-Based Training (Excelling in Surgical Training) -- Strategies for Succeeding During Intern Year: Perspectives from Recent Surgical Interns -- Strategies for Succeeding in Residency Programs: A Program Director's Perspective -- Part IV: Building a Career in Academic Surgery -- Balancing Clinical, Research, and Teaching Responsibilities -- Understanding The Intersection of Social Media and Mentorship in Surgery and Medicine -- Part V: Work-Life Integration as an Academic Surgeon -- Fostering Productive Mentor-Mentee Relationships -- Achieving Personal and Professional Fulfilment -- Part VI: Embracing Diversity and Inclusion in Surgery -- The Resident Perspective - A Part of and Apart from the Surgical Workforce -- Recognizing Unconscious Bias and Its Impact on Patient Care and Outcomes -- Strategies for Promoting Diversity and inclusion in Surgical Specialties -- Understanding the Importance of Self Care and Mental Health.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Surgery; Practice of medicine; Hospitals -- Administration; General Surgery; Practice and Hospital Management